2003
DOI: 10.1161/01.cir.0000057982.50167.6e
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Low-Density Lipoprotein Particle Size, Plasma Lipoproteins, and Progression of Coronary Artery Disease

Abstract: on behalf of the DAIS GroupBackground-The Diabetes Atherosclerosis Intervention Study showed that treatment with fenofibrate decreases progression of coronary atherosclerosis in subjects with type 2 diabetes. We determined whether on-treatment plasma lipid concentrations and LDL particle size contribute to the favorable effect of fenofibrate on the progression of coronary artery disease (CAD). Methods and Results-A total of 418 subjects with type 2 diabetes were randomly assigned to 200 mg micronized fenofibra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(35 citation statements)
references
References 35 publications
0
35
0
Order By: Relevance
“…Recent studies have found that plasma sd-LDL levels were influenced by other risk factors such as gender, age, glucose, body mass index and conventional lipid parameters [19, 21, 27]. In our study, multiple stepwise regression analysis showed that sd-LDL was significantly and positively associated with TG, systolic blood pressure, and history of DM, with strong negative correlations with HDL cholesterol (RC = 6.21) as well as LDL cholesterol (RC = 2.07).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found that plasma sd-LDL levels were influenced by other risk factors such as gender, age, glucose, body mass index and conventional lipid parameters [19, 21, 27]. In our study, multiple stepwise regression analysis showed that sd-LDL was significantly and positively associated with TG, systolic blood pressure, and history of DM, with strong negative correlations with HDL cholesterol (RC = 6.21) as well as LDL cholesterol (RC = 2.07).…”
Section: Discussionmentioning
confidence: 99%
“…Compared with placebo, fenofibrate treatment significantly increased LDL particle size and HDL cholesterol and decreased plasma total cholesterol, LDL cholesterol, and triglyceride concentrations. The final LDL particle size was inversely correlated with the increase in percentage diameter stenosis (Vakkilainen et al, 2003).…”
Section: Relationship Between Insulin Resistance Diabetes and Smallmentioning
confidence: 93%
“…These changes in the NMR lipoprotein subclass profile predictably increased the risk of cardiovascular disease but were not fully apparent in the conventional lipid profile (Garvey et al, 2003). The Diabetes Atherosclerosis Intervention Study (DAIS) (Vakkilainen et al, 2003) showed that lipid-modifying treatment decreased the angiographic progression of coronary atherosclerosis in subjects with type 2 diabetes. This effect was related in part to the correction of lipoprotein abnormalities.…”
Section: Relationship Between Insulin Resistance Diabetes and Smallmentioning
confidence: 99%
“…In general, LDL particles can be subfractionated into buoyant, intermediate, and dense LDLs. In vitro experiments (3)(4)(5) and epidemiologic studies (6)(7)(8)(9)(10)(11)(12) have shown that buoyant LDLs (12) and particularly dense LDLs (6)(7)(8)(9)(10)(11) are more atherogenic than intermediate LDLs. Such findings may be partly explained by the association of dense LDLs with increased levels of plasma triglycerides and decreased levels of HDL-cholesterol (8).…”
mentioning
confidence: 99%